Where are the species limits? Morphology versus genetics in Neotropical chewing lice of the genus Myrsidea (Phthiraptera: Menoponidae), with description of three new species - Kolencik, Stanislav; Sychra, Oldrich; Papousek, Ivo; Literak, Ivan (Zootaxa, 2017)
Eleven species of lice of the genus Myrsidea Waterston, 1915 (Phthiraptera: Menoponidae) from passerine birds (Passeriformes: Cardinalidae, Fringillidae, Thraupidae) in the Neotropical Region are recorded and discussed. They include three new species with hosts in the family Thraupidae from Paraguay, which are described and illustrated: Myrsidea flaveolae new species ex Sicalis flaveola, Myrsidea habiae new species ex Habia rubica, and Myrsidea sayacae new species ex Thraupis sayaca. Five other previously known Myrsidea species are included with new data on intraspecific morphological variability, hosts associations and geographical distribution, as follows: Myrsidea coronatae, M. lightae, M. rufi, M. seminuda, and M. violaceae. Three further species are recorded at genus level only due to lack of adequate material. A 379 bp portion of the mitochondrial cytochrome oxidase I (COI) gene was sequenced in order to assess relative genetic divergence among Myrsidea populations. The application of intra- and interspecific sequence divergences as predictor of species boundaries in the taxonomy of this megadiverse genus is discussed.